The effectiveness of the "Scamper" program in developing creative thinking in children with a movement disability: Examples of imaginative games - Adel, Hiba Asmaeesl (Journal of Educational and Psychological Sciences, 2022)
This study aimed to investigate the effectiveness of the "Scamper" program for imaginative play on developing creative thinking among children with a movement disability, between (9-11) years, based on the experimental method. An officer, consisting of (20) boys and girls. This experiment was conducted in the city of Mahdia with the help of the Al-Ansar Association for Persons with Disabilities, and to achieve the purpose of the study, then the “Scamper” program for imaginative games was implemented for 5 sessions per month. The arithmetic averages and the value of (t) and its significance were calculated for the performance of the control and experimental groups on the pre and post test. The results of the study showed; that there are differences between the average scores of creative thinking between the experimental and control group; In favor of the experimental group in all of the fluency skill, flexibility skill, originality skill and creative thinking in a totality. Based on the results, the researcher recommended directing educational programs for children with a movement disability to the need to pay attention to the development of innovative thinking through the provision and design of programs based on play, given its great importance in childhood, and relying on the Scamper program and its integration as one of the educational mechanisms in order to rehabilitate people with disabilities., In addition to proposals for complementary studies on the subject; It shows the importance of the need to build training programs for the development of creative thinking for people with motor disabilities at different stages and the extent to which different types of play affect the development of creative thinking skills.